Genetic and Chemical Diversity in Perovskia abrotanoides Kar. (Lamiaceae) Populations Based on ISSRs Markers and Essential Oils Profile. Issue 3 (13th March 2018) - Pourhosseini, Seyyed Hossein; Hadian, Javad; Sonboli, Ali; Nejad Ebrahimi, Samad; Mirjalili, Mohammad Hossein
Abstract : Genetic and the essential oil composition variability among twelve Perovskia abrotanoides populations ( PAbPs ) growing wild in Iran were assessed by ISSR markers, GC‐FID and GC/MS, respectively. Nine selected ISSR primers produced 119 discernible bands, of them 96 (80.7%) being polymorphic. Genetic similarity values among populations ranged between 0.07 and 0.79 which indicated a high level of genetic variation. Polymorphic information content, resolving power and marker index generated by ISSR primers were, 0.31, 6.14, and 3.32, respectively. UPGMA grouped PAbPs into four main clusters. Altogether, 38 chemical compounds were identified in the oils, and a relatively high variation in their contents was found. Camphor (11.9 – 27.5%), 1, 8‐cineole (11.3 – 21.3%), α ‐bisabolol (0.0 – 13.1%), α ‐pinene (5.9 – 10.8%), and δ ‐3‐carene (0.1 – 10.5%) were the major compounds. Oxygenated monoterpenes (32.1 – 35.8%) and monoterpene hydrocarbons (25.7 – 30.4%) were the main groups of compounds in the oils studied. Cluster analysis and principal‐component analysis were used to characterize the samples according to oil components. Four main chemotypes were found to be Chemotype I (camphor/1, 8‐cineol), Chemotype II (1, 8‐cineole/camphor), Chemotype III (camphor/1, 8‐cineol/ α ‐bisabolol), and Chemotype IV (camphor/ δ ‐3‐carene/ α ‐bisabolol). The information, provided here on P . abrotanoides populations, will be useful to introduce this plant into agricultural systems. Abstract :